Pembelajaran tematik berbasis kearifan lokal di Sekolah Dasar dalam menghadapi masyarakat ekonomi ASEAN (MEA) - Unga Utari; I Nyoman Sudana Degeng; Sa’dun Akbar (Universitas Negeri Malang, 2016)
This research aims to unravel the role of the values of local wisdom in the face of the MEAs through thematic learning. Some research and development based on local wisdom that has been done by previous researchers intended to facilitate students in achieving the learning is not only conceptually but also applicable. Local knowledge is essential considering that learning happens in the classroom, especially in primary school students should start with the closest or the world that is often encountered by students. The values of local knowledge will help students understand each concept in the material so that the stock of knowledge gained students not only to the limited knowledge alone, but can also be implemented in the form of students practice outside the school. Thematic learning based on local wisdom will be connected in a hang of students to act properly in the face of the MEA. Civilization is not only the man is not only omniscient but versatile to advance the State.Keywords: Local Wisdom, the Asean Economic Community (AEC), Thematic Learning http://dx.doi.org/10.17977/um022v1i12016p039